The dress and individual differences in the perception of surface properties. (December 2017) - Witzel, Christoph; O'Regan, J. Kevin; Hansmann-Roth, Sabrina
Graphical abstract: Highlights: A relationship between individual differences in #theDress and colour constancy. Different kinds of individual differences in the perception of surface properties. A simple and reliable method to measure the continuous perception of #theDress. Abstract: This study investigates systematic individual differences in the way observers perceive different kinds of surface properties and their relationship to the dress, which shows striking individual differences in colour perception. We tested whether these individual differences have a common source, namely differences in perceptual strategies according to which observers attribute features in two-dimensional images to surfaces or to their illumination. First, we reanalysed data from two previous experiments on the dress and colour constancy. The comparison of the two experiments revealed that the colour perception of the dress is strongly related to individual differences in colour constancy. Second, two online surveys measured individual differences in the perception of colour-ambiguous images including the dress, in colour constancy, in gloss perception, in the subjective grey-point, in colour naming, and in the perception of an image with ambiguous shading. The results of the surveys replicated and extended previous findings according to which individual differences in the colour perception of the dress are due to implicit assumptions about the illumination. However, results also showed that the individual differences for other phenomena were independent of the dress and of each other. Overall, these results suggest that the striking individual differences in dress colour perception are due to individual differences in the interpretation of illumination cues to achieve colour constancy. At the same time, they undermine the idea of an overall perceptual strategy that encompasses other phenomena more generally related to the interpretation of illumination and surface properties.